SYNTHESIS, CHARACTERIZATION, CYTOTOXICITY AND ANTIMICROBIAL STUDIES OF SCHIFF BASE DERIVED FROM 2-BENZOYLBENZOIC ACID AND 4-NITRO ANILINE AND ITS METAL(II) COMPLEXES (FUDMA JOURNAL OF SCIENCES, 2024)
Schiff base derived from 4-nitro aniline and 2-benzoylbenzoic acid, and its Mn(II), Co(II) and Ni(II) complexes have been synthesized and characterized based on their melting/decomposition temperature, solubility, magnetic and infrared analysis. Gravimetric analysis and Job’s method of continuous variation reveal that all metal complexes are in 1:2 metal-ligand ratios. All complexes have low conductance value (13.6-20.6 ohm-1cm-1mol-1), indicating that they are non-electrolyte. However the cytotoxic analysis indicates that Co(II) complex was more toxic with the LC50 value of 181.72 ug/ml than the other complexes. The Schiff base and its respective metal complexes were screened for their antimicrobial activities and the results revealed that the compounds showed significant activity against all isolates.
Keywords: Schiff base; 2-benzoylbenzoic acid; 4-nitro aniline; Metal complexes; Antimicrobial activity; Solubility; Cytotoxicity activity